Results of Sulphur Fertilization Experiment with Oilseed Rape - Puy, Katalin; Győri, Zoltán (Acta Agraria Debreceniensis, 2020)
The rape is definitely a sulphur-demanding crop, which yield and the quality of its oil is threaten by the emerging shortage of sulphur nowadays. We made sulphur fertilising trials on two places in the northeastern rape growing area (in Felsőzsolca and Mezőkövesd), in the season 2001/2002. We compared the result the 5 five treating set in 2 repeats on brown forest soil with the results of the control plots. We used FitoHorm 32 S sulphur solution as sulphur fertiliser, with the dose of 3, 6 and 10 litres per hectare, as well as the joint effects of sulphur and boron; and the effect of boron alone. On the assessment of our results we looked for relation between the sulphur fertilising, the seed production, the oil content and the protein content.